Cytomegalic inclusion disease in the adult. Issue 3 (May 1968) - Evans, D. J.; Williams, E. D.
Abstract : The distribution of infected cells in 13 necropsies on adults with cytomegalovirus disease is reported and discussed in relation to the local damage caused by the infection and predisposing factors. The distribution, with lung as the most common site, but other organs such as thyroid, liver, and colon not infrequently involved, agrees fairly well with other series. No heavy infection confined to one organ was found, and it is concluded that a truly localized infection in the adult probably does not occur. Evidence of destructive inflammatory changes attributable to the virus was scanty; a lymphocyte and plasma cell infiltrate was sometimes found, and microglial nodules were found in a case with inclusions in the brain. In one case heavy cytomegalovirus infection in the colon was associated with, and probably caused, marked colonic ulceration which led to the death of the patient. The major predisposing factor to infection in this series was corticosteroid therapy: eight of the 13 patients had been treated with steroids and one had Cushing's syndrome associated with a bronchial carcinoma. Three of the other four patients had a very few inclusions only. Adrenal involvement was not found in any of the steroid-treated patients but was present in two of the four patients not treated with steroids where adrenal sections were available. It is concluded that most adult patients with cytomegalovirus infection have impaired immune mechanisms, and that heavy infection may rarely lead to a clinically serious disease.